On the Influence of Vanadium on Air‐Hardening Medium Manganese Steels for Sustainable Forging Products. Issue 6 (15th January 2021) - Gramlich, Alexander; Middleton, Aaron; Schmidt, Rolf; Krupp, Ulrich
Abstract : A new alloy for drive‐train applications with a significant addition of vanadium is presented. The influence of vanadium addition to air‐hardening forging steels is investigated and discussed. For the investigations, a laboratory melt is casted and forged into a rod. The mechanical properties and the microstructure of the new alloy are described and compared with a vanadium‐free reference alloy from a previous study. The forged component shows high strength and hardness in the as‐forged state (YS: 892 MPa, UTS: 1366 MPa, hardness: 430 HV30) distributed equally over the full cross‐section. In addition, the strength does not decrease during subsequent heat treatments enabling the application as a material for surface treatments such as nitriding or plasma nitriding. Although strength, ductility, and hardness change as expected with increasing tempering, toughness acts different than in vanadium‐free alloys during intercritical annealing which hints at the interaction of vanadium with the fracture mechanism. Abstract : A new medium manganese steel with vanadium addition for automotive forging application is presented. The steel is alloyed with 4 wt% aluminum to assure a complete martensitic microstructure after air‐cooling. The investigated laboratory melt (80 kg), reaches a yield strength of 892 MPa and a Charpy‐V notch impact toughness of 48 J in the air‐cooled condition.